2013
DOI: 10.1177/0022034513483142
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Disease and Rheumatoid Arthritis

Abstract: This systematic review considers the evidence available for a relationship between periodontal disease and rheumatoid arthritis. MEDLINE/PubMed, CINAHL, DOSS, Embase, Scopus, Web of Knowledge, MedNar, and ProQuest Theses and Dissertations were searched from the inception of the database until June 2012 for any quantitative studies that examined the association between periodontal disease and rheumatoid arthritis. Nineteen studies met our inclusion criteria. Good evidence was found to support an association bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
116
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(132 citation statements)
references
References 39 publications
4
116
0
4
Order By: Relevance
“…As players in the etiology of periodontal disease, several oral bacteria have been studied for association with RA etiology. Clinical studies have detected P. gingivalis, Prevotella intermedia , and Prevotella nigrescens DNA in sera and synovial fluids of RA patients [56], and antibodies against P. gingivalis, A. actinomycetemcomitans and few other oral microbiota constituents have also been found in sera of patients suffering from RA, compared to healthy controls [53, 54]. …”
Section: Rheumatoid Arthritis and Oral Microbesmentioning
confidence: 99%
“…As players in the etiology of periodontal disease, several oral bacteria have been studied for association with RA etiology. Clinical studies have detected P. gingivalis, Prevotella intermedia , and Prevotella nigrescens DNA in sera and synovial fluids of RA patients [56], and antibodies against P. gingivalis, A. actinomycetemcomitans and few other oral microbiota constituents have also been found in sera of patients suffering from RA, compared to healthy controls [53, 54]. …”
Section: Rheumatoid Arthritis and Oral Microbesmentioning
confidence: 99%
“…One such inflammatory disease, periodontitis, has a multifactorial etiology which is influenced by host genetics and several environmental factors. Further, there is evidence that this inflammatory disease affecting the periodontium represents an increased risk for several systemic diseases, including atherosclerosis (1), diabetes (2), and rheumatoid arthritis (3,4). Historically, periodontal disease is associated with several pathogens contributing to a complex microbial milieu which can initiate or directly contribute to host tissue destruction (5).…”
mentioning
confidence: 99%
“…In this study, ESR was increased in patients who had a higher temperature, and 90% of these were in the group suffering from periodontitis. However, in a systematic review, it was concluded that ESR as a value is an inconclusive parameter, and that results based on it should be interpreted with caution [32]. …”
Section: Discussionmentioning
confidence: 99%